Micro/Nanolithography A Heuristic Aspect on the Enduring Technology - Thirumalai, Jagannathan (IntechOpen, 2018)
The main objective of this book is to give proficient people a comprehensive review of up-to-date global improvements in hypothetical and experimental evidences, perspectives and prospects of some newsworthy instrumentation and its numerous technological applications for a wide range of lithographic fabrication techniques. The present theme of this book is concomitant with the lithographic ways and means of deposition, optimization parameters and their wide technological applications. This book consists of six chapters comprehending with eminence of lithography, fabrication and reproduction of periodic nanopyramid structures using UV nanoimprint lithography for solar cell applications, large-area nanoimprint lithography and applications, micro-/nanopatterning on polymers, OPC under immersion lithography associated to novel luminescence applications, achromatic Talbot lithography (ATL) and the soft X-ray interference lithography. Individual chapters provide a base for a wide range of readers from different fiels, students and researchers, who may be doing research pertinent to the topics discussed in this book and find basic as well as advanced principles of designated subjects related to these phenomena explained plainly. The book contains six chapters by experts in different fields of lithographic fabrication and technology from over 15 research institutes across the globe.